1988
DOI: 10.1111/j.1471-0528.1988.tb06860.x
|View full text |Cite
|
Sign up to set email alerts
|

Beta‐mimetics in preterm labour: an overview of the randomized controlled trials

Abstract: 1976) Contribution of preterm delivery to perinatal mortality. Br Med J 2, 965. (1973) Prostaglandin F2a concentrations in peripheral blood during the first stage of normal labour. Br Med J 1,709-71 1. Tumbull A. C. (1957) Uterine contractions in normal and abnormal labour. J Obstet Gynaecol Brit Emp 64, 321. Uldbjerg N. (1989) Cervical connective tissue in relation to pregnancy, labour and treatment with prostaglandin E,. Acta Obstet Gynecol Scand Suppl148.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
108
0
8

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 326 publications
(124 citation statements)
references
References 18 publications
8
108
0
8
Order By: Relevance
“…Consequently, women presenting with threatened preterm labor are often treated with hospitalization and the administration of tocolytics to avoid preterm delivery. Randomized studies on the use of tocolytics in threatened preterm labor have demonstrated a significant prolongation of pregnancy by about 7 days but no significant reduction in perinatal mortality or morbidity 1,2 . Furthermore, many studies have shown that more than 70% of women presenting with threatened preterm labor are not in true labor and do not deliver within 7 days 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, women presenting with threatened preterm labor are often treated with hospitalization and the administration of tocolytics to avoid preterm delivery. Randomized studies on the use of tocolytics in threatened preterm labor have demonstrated a significant prolongation of pregnancy by about 7 days but no significant reduction in perinatal mortality or morbidity 1,2 . Furthermore, many studies have shown that more than 70% of women presenting with threatened preterm labor are not in true labor and do not deliver within 7 days 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The observations reported in the present study also confirmed the results from the above meta-analysis. 25 Isoxsuprine was the most frequently used tocolytic in the present study. Overall among patients receiving pharmacological management for PTL, there was an increase in gestation period with favourable pregnancy outcome in those receiving isoxsuprine.…”
mentioning
confidence: 93%
“…Sir, We agree that meta-analysis of p-mimetic therapy has not yet shown any benefit in terms of improved perinatal mortality or severe respiratory disorders but has shown a greater effect than placebo in delaying delivery for at least 24 h and in reducing the proportion of babies born before 37 weeks (King 1987). Time may be gained for antenatal steroid administration or to facilitate in utero trasnfer to a site where an intensive care cot is available.…”
Section: Author's Replymentioning
confidence: 99%
“…The incidence of preterm delivery can be measured with ease, but when quoted the distribution of gestational ages at delivery much also be stated. The majority of deaths occur in the minority of preterm pregnancies that terminate before 32 wceks (King et al 1988). Perinatal outcome encompasses mortality as a likely consequence of preterm delivery and short and long term morbidity, which may have a complex aetiology.…”
Section: Author's Replymentioning
confidence: 99%
See 1 more Smart Citation